PENGEMBANGAN MODUL BIOMOLEKUL DAN METABOLISME DENGAN PARADIGMA UNITY OF SCIENCES DAN GROWTH MINDSET - Ratih Rizqi Nirwana; Rikha Fitriyana (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2018)
This research is a research and development aiming to develop Biochemistry lecture module on Biomolecule and Metabolism Material with Unity of Sciences and Growth mindset paradigm, as well as to test its effectiveness. This research uses Sugiyono model and implemented in the Department of Chemistry Education. The validation of products is carried out by religious experts and biochemists. Trials were conducted 2 times, in small groups and large groups that received biochemistry courses. The result of validation by religious experts is 92% and biochemist 88%. Based on the improved aspects of cognitive learning outcomes and learners' responses, the modules developed having high effectiveness. This is shown by the results of cognitive learning small classes show mastery of 85% and large classes reached 79%. While the responses of small class students obtained the score 84%, and 75% of the large class students.